A study on epistaxis in adults: a series of 120 cases - R., Nanmullai; V. J., Vikram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Epistaxis is a symptom of many diverse conditions. This study on epistaxis of 120 cases in adults, is to find out the most common causes for epistaxis, prevalence of epistaxis in either sex, age groups and for early identification of cause and management. Results were analysed. Methods: Prospective study of series 120 cases in adults. Results: Results were analysed and idiopathic was most common cause of epistaxis, males were more affected than females, and the most common age group affected is 13 to 30 years. Most cases are treated by conservative measures. Conclusions: Idiopathic is the most common cause of epistaxis in this present study. Other causes are trauma, DNS with spurs, sinusitis and JNA in adolescent males. Males are commonly affected than females .The most common age group affected is 13 to 30 years and 41 to 60 years. Most cases are treated by conservative measures.